SISTEM MONITORING DATA METERAN AIR PELANGGAN PDAM MENGGUNAKAN MIKROKONTROLER ATMEGA 16 - Herdianto Herdianto; Ayu Nuriana Sebayang; Darmeli Nasution (STMIK Budi Darma, 2017)
The purpose of this research is to design a monitoring system of PDAM customer water meter data using ATMEGA 16 microcontroller and to know the accuracy of the system that has been designed. The results of this research will be expected to help the PDAM (local water company) in overcoming the existing problems regarding the recording of water meter data is not accurate. In this research there are 5 sample of meter data which used by method used is demonstration application. In the research of monitoring system of customer water meter data there are 2 forms of testing conducted that is the testing of water flowmeter sensor and data transmission GSM SIM 800. From the test results accuracy of flowmeter water sensor reaches 100% while GSM SIM 800 data transmission only 95%.